REPRESENTASI PEKERJA PEREMPUAN DI BALI DALAM FOTO JURNALISTIK PADA GETTY IMAGES - YUSUF, NAUFAL FIKRI; JONI, I DEWA AYU SUGIARICA; SURYAWATI, I GUSTI AGUNG ALIT (E-Jurnal Medium, 2024)
This research purpose is presenting about female woker in Bali by Anton Raharjo on Getty Images. The researcher exclusively analyze gender message or role and women position inside the researched photos with qualitative research methods and Semiotics Roland Barthes Theory for finding denotation meaning, connotation and myth. This research giving a fact that there are double burden carrying by female construction workers in Bali, causing exploitation and alienation. The existence of women in public still considered as an additional breadwinner for the family. Beside that, the existence of female construction workers often being ignored because of the difference wages received by male workers. Moreover, female construction workers still considered 2nd class with stereotype that are attached to women in public.   Key Words : Gender, women position, semiotics, construction workers, stereotype.